Уцелевший «Свадебный обряд» - Исраелян, Астхик (Институт языкознания РАН)
Статья посвящена арцахскому карпету (безворсовый ковер), который находится в частной коллекции в Ереване. Карпет был создан Соной Акопян в 1904 году в селе Чартар Мартунинского района Арцаха (Нагорный Карабах) и был преобретен у ее родственников, бежавших из Баку в 1990 г. Яркое по цветовой гамме изделие имеет довольно большой размер (497см х 205см) и выткано в двусторонней технике, каждый цвет имеет свое значение и служит определенным знаком. The studied napless carpet which is now in Yerevan was obtained from refugees from Baku in 1990. They were the relatives of Sona Hakobyan, who has made the carpet in Chartar village, Martuni region in Artsakh, in 1904. Armenian carpets in general have а large number of different functions. They were of particular importance in marriage, because they were an important Астхик Исраелян component of the bride's dowry. This carpet was also made especially for the dowry. That is why the wedding ritual is “described” here by using the traditional patterns and compositions typical of Artsakh. It has different symbols, images of especially significant actions, necessary items and participants of the ceremony.
Keywords: Фольклористика; Этнография